(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses the ecological characteristics of bees belonging to the family Hymenoptera: Megachilidae in the Tashkent oasis, their behavior as a result of their interactions, their importance in the pollination process, and their importance in agrocenoses.